Promotive, preventive, and treatment interventions for adolescent mental health in sub-Saharan Africa: A protocol for two scoping reviews including systematic analyses of intervention effectiveness. - James Steel; Fantacy Twagira; Maaike L Seekles; Angela I Obasi (PLoS ONE, 2022)
Introduction The increasing prevalence of mental health difficulties amongst adolescents is a worldwide concern. Poor mental health in adolescence is associated with a range of mental, physical and social problems in later life. In sub-Saharan Africa, limited data suggests that mental disorders amongst adolescents are common. It is important that interventions to address this are rooted in an understanding of the unique local context and culture. Yet, the current use, development, and effectiveness of adolescent mental health interventions in sub-Saharan Africa is unclear. In response, this paper presents a protocol for two scoping reviews that together will examine the available evidence on promotive, preventive, and treatment interventions for adolescent mental health in sub-Saharan Africa. Methods and analysis The scoping reviews will follow the five-step methodological framework proposed by Arksey and O'Malley, with further recommendations from the Joanna Briggs Institute. They will review scientific and grey literature published between 2000 and 2021, without restrictions in language or study type. A wide range of sources, including MEDLINE, CINAHL, Global Health, PsychINFO, Cochrane and Google Scholar will be searched. Eligibility screening and data extraction will be done by two independent reviewers, and disagreements resolved by a third reviewer. Data will be summarised in two phases. A narrative synthesis will provide a descriptive profile of all studies included and will explore key concepts related to intervention types, target populations and adaptations to local context. A systematic review element will collate evidence of intervention effectiveness from (cluster) Randomised Controlled Trials. Discussion and dissemination To the best of our knowledge, these scoping reviews are the first to synthesise a wide range of available evidence on promotive, preventive and treatment interventions for adolescent mental health in sub-Saharan Africa. The results will be published in peer-reviewed publications and will be presented as an evidence base for future intervention development and implementation.